On Integration of Error Concealment and Authentication in JPEG2000 Coded Images - Memon, Qurban A (European Journal of Applied Sciences, 2014)
Nowadays, it is widely understood that data compression is not only essential to speed up the transmission rate but also to provide other gains like low storage. In order to counter data manipulations and tampering during transmission, the image authentication has turned out to be equally important. But the drawback of compressed data transmission is that the compressed data are susceptible to channel impairments. In this paper, an error concealment approach is integrated with low cost image authentication scheme to benefit better visual quality as well as content author and user satisfaction. The image authentication includes content based digital signature that is watermarked and diffused in the whole image before JPEG2000 coding. To tackle noise, the error detection and concealment technology is examined to include edge information as part of error concealment approach. The edge image is sent along with JPEG2000 coded image to determine corrupted coefficients. The simulation results are conducted on test images for different values of bit error rate to judge confidence in noise concealment within the received images.